High Stock Returns before Holidays: Existence and Evidence on Possible Causes - Ariel, Robert A. (Journal of Finance, 1990)
On the trading day prior to holidays, stocks advance with disproportionate frequency and show high mean returns averaging nine to fourteen times the mean return for the remaining days of the year. Over one third of the total return accruing to the market portfolio over the 1963–1982 period was earned on the eight trading days which each year fall before holiday market closings. Examination of hourly pre-holiday stock returns reveals high returns throughout the day. Pre-holiday stock returns in the post-test 1983–1986 period are also examined.